2019
DOI: 10.3390/cancers11070904
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling in Cancer Metabolism and Immunity

Abstract: The Wingless (Wnt)/β-catenin pathway has long been associated with tumorigenesis, tumor plasticity, and tumor-initiating cells called cancer stem cells (CSCs). Wnt signaling has recently been implicated in the metabolic reprogramming of cancer cells. Aberrant Wnt signaling is considered to be a driver of metabolic alterations of glycolysis, glutaminolysis, and lipogenesis, processes essential to the survival of bulk and CSC populations. Over the past decade, the Wnt pathway has also been shown to regulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 121 publications
2
85
0
Order By: Relevance
“…Wnt/β-catenin signaling is associated with CSC properties. Activation of Wnt/β-catenin signaling orchestrates the self-renewal of CSCs and induces several stemness factors, such as OCT4, SOX2, and CD44 [114,115]. Members of the secreted frizzled-related protein (SFRP) family are Wnt antagonists and inactivate Wnt ligands, impairing signaling pathways from FZD receptors and low-density lipoprotein receptor-related proteins (LRPs) [114].…”
Section: Wnt/β-catenin Signaling and Cscsmentioning
confidence: 99%
“…Wnt/β-catenin signaling is associated with CSC properties. Activation of Wnt/β-catenin signaling orchestrates the self-renewal of CSCs and induces several stemness factors, such as OCT4, SOX2, and CD44 [114,115]. Members of the secreted frizzled-related protein (SFRP) family are Wnt antagonists and inactivate Wnt ligands, impairing signaling pathways from FZD receptors and low-density lipoprotein receptor-related proteins (LRPs) [114].…”
Section: Wnt/β-catenin Signaling and Cscsmentioning
confidence: 99%
“…Aberrant Wnt signaling leads to metabolic alterations in cancer cells that are critical for their survival and proliferation (60). Interestingly, Wnt signaling also plays an important role in the metabolic reprogramming of DCs in the TME (60,61). Cellular metabolic pathways play a critical role in modulating the functions of DCs (61)(62)(63).…”
Section: Metabolic Reprogramming Of Dcs By Wntsmentioning
confidence: 99%
“…Cellular metabolic pathways play a critical role in modulating the functions of DCs (61)(62)(63). Emerging evidence show that potential metabolic differences exist among DC subsets and also between tolerogenic and immunogenic DCs (60,62). Immature or tolerogenic DCs show a catabolic metabolism that is manifested by increased oxidative phosphorylation, fatty acid oxidation (FAO), and glutaminolysis (61,63,64).…”
Section: Metabolic Reprogramming Of Dcs By Wntsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt signaling pathway seems to play a significant role in immunological reactions (El-Sahli, Xie, Wang, & Liu, 2019), so that it has been shown that stimulation of the Wnt signaling pathway is associated with lower immune cell infiltration in tumor site (Luke, Bao, Sweis, Spranger, & Gajewski, 2019), requiring to expand our understanding towards the Wnt pathway. On the basis of the modulatory impact of Wnt pathway on immunological reactions, targeting this pathway can be beneficial in the treatment of inflammatory disorders such as rheumatoid arthritis (RA).…”
Section: Immunomodulatory Activitymentioning
confidence: 99%